The sexual behavior of young people living with a disability: Findings from the KAP study in Northern Uganda - Bukuluki, Paul; Wandiembe, Symon Peter; Kisaakye, Peter; Kiwujja, Victor; Kajungu, Christine; Mugwanya, Wilberforce; Nabakooza, Shakira; Anyii, Cyprian (Frontiers in Reproductive Health, 2023)
Young people living with disability form one of the most vulnerable population groups globally. There is limited information on the use of SRH services among young people living with a disability. This analysis is based on household survey data among young people. Drawing on a sample of 861 young people living with a disability (15-24 years), we investigate the sexual behaviour, and identify the risk factors associated with sexual behavior of young people living with a disability. Multilevel logistic regression was used. Results indicate that risky sexual behaviour was associated with alcohol consumption (aOR = 1.68; 95%CI: 0.97, 3.01), having limited knowledge of HIV and STI prevention methods (aOR = 6.03; 95%CI: 0.99, 30.00), and low life skills (aOR = 4.23; 95%CI: 1.59, 12.87). The odds of not using a condom at last sex were significantly higher among in-school young people than out of school young people (aOR= 0.34; 95%CI: 0.12, 0.99). Targeted interventions aimed at reaching out to young people living with a disability should consider their sexual and reproductive health needs, barriers, and facilitators. Interventions can also promote self-efficacy and agency of young people living with a disability in making informed sexual and reproductive health choices.